Letter - Schevenels, Walther, b. 1894
026-0128-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, AVENUE D'ORSAY, PARIS-VIIe EXECUTIVE COMMITTEE: President: W. M Citrine, Great Britain Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia General Secretary: W. Schevenels TELEGRAMS: interfed-paris TELEPHONE: invalides 45-88 Letter Sec. ref. div. No. 313 AFFILIATED COUNTRIES: Argentine Austria Belgium Canada Czechoslovakia Danzig Denmark Dutch East Indies Estonia Finland France Great Britain Greece Holland Hungary India Luxemburg Memel Territory Mexico Norway Palestine Poland Roumania South Africa South-West Africa Spain Sweden Switzerland Yugoslavia 6th April, 1939 Mr. H.V. Tewson, Transport House, Smith Square, London, S.W.1. Dear Vincent, In reply to yours of the 4th April regarding Pascual Tomas-Taengua, I am glad to tell you that from the very beginning we have tried to help him in every possible way. First of all our Committee sent him 500 francs and another Committee also sent him a reasonable sum, and we are now trying to obtain a permit for him to live near Paris, so that you may rely upon us to do everything that can be done for him. You must not, however, overestimate our influence in France. In spite of the most pressing steps taken by influential people like Jouhaux, Vincent Auriol and Blum, we fail in many cases to obtain the desired results for our Spanish comrades. Yours sincerely, W. Schevenels. General Secretary. 292/946/26/128